1998
DOI: 10.1086/515670
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Regulation of Interferon‐γ, Interleukin‐12, and Tumor Necrosis Factor‐α in Human Interferon‐g Receptor 1 Deficiency

Abstract: Mycobacterial infections are critically controlled by interferon-gamma (IFN-gamma) and the cellular responses it elaborates, as shown by patients with mutations in the IFN-gamma receptor ligand-binding chain (IFN-gamma R1) who have disseminated nontuberculous mycobacterial infections. The immunologic sequelae of IFN-gamma R1 deficiency were characterized in 2 unrelated patients from the Indian subcontinent with novel homozygous recessive IFN-gamma R1 mutations. In vitro, these patients' peripheral blood mononu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
89
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(90 citation statements)
references
References 4 publications
0
89
0
1
Order By: Relevance
“…They started to examine candidate genes and found that mutations in the IFNgR1 gene could lead to disseminated BCG infection at the same time as Levin's group found they caused recurrent atypical mycobacterial infections. 80 The IFNgR1 gene mutations are inherited as autosomal recessive traits and either abolish receptor expression 78,[80][81][82][83][84][85] or binding of the receptor to IFNg. [86][87] Partial IFNgR1 deficiency has also been described in two siblings, one of whom developed disseminated BCG infection and the other clinical tuberculosis.…”
Section: Familial Atypical Mycobacteriosis and Abnormal Ifng Signallingmentioning
confidence: 99%
“…They started to examine candidate genes and found that mutations in the IFNgR1 gene could lead to disseminated BCG infection at the same time as Levin's group found they caused recurrent atypical mycobacterial infections. 80 The IFNgR1 gene mutations are inherited as autosomal recessive traits and either abolish receptor expression 78,[80][81][82][83][84][85] or binding of the receptor to IFNg. [86][87] Partial IFNgR1 deficiency has also been described in two siblings, one of whom developed disseminated BCG infection and the other clinical tuberculosis.…”
Section: Familial Atypical Mycobacteriosis and Abnormal Ifng Signallingmentioning
confidence: 99%
“…Mutations in five different genes produce this disorder: IFN-GR1, IFN-GR2, STAT1, IL12B, and IL12RB1. The main clinical characteristic of these patients is their higher susceptibility to the development of disseminated mycobacterial disease or local recurrent infections by non-tuberculosis mycobacteria and, in some cases, chronic infections by other agents such as Salmonella species and certain viruses (20,(22)(23)(24)(25)(26)(27)(29)(30)(31)(32)(33)(34)(35)(36). Many of these characteristics are similar to the clinical features observed in our patients (Table 3); therefore, a defect in one of the molecules involved in the IL-12/IFN-γ/IFN-γR/STAT-1 activation pathway is a possible explanation for their phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…These patients exhibit systemic infections and inability to develop mature granulomas in response to mycobacteria and frequently die as a consequence of this infection. Microorganisms other than mycobacteria such as Salmonella and some viruses also produce severe infections (20)(21)(22)(23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
“…Among all these cells, CD4 and CD8 T cells are important in producing INF-γ, one of the main cytokines involved in the immune response. Its importance has been shown in some studies [7][8][9][10] where INF-γ gene knockout or the lack of its receptor led to higher susceptibility to Mycobacterium tuberculosis.…”
Section: Importance Of Cellular Immunity In Tuberculosismentioning
confidence: 99%